An American Constitutional History Course for Non-American Students - Grau, Luis (Historia del Derecho, 2012)
Certain attributes of American life hold a special attraction to people all over the world, regardless of their social or political beliefs. Often those familiar features are simple banalities of that 'American way,' while more profound and remarkable traits of that complex nation seem to have gone almost unnoticed outside its borders, although their prevalent influence is evident. Current technology, business ways, commerce, culture, etc., are all deeply marked by that country 'ways.' Unquestionably, the American constitutional system is one of these hidden traits that, regardless of the circumstances, is present all over our -so called- Western world. Nevertheless, it is, for most and to most, unknown. Responses to the previous works by this author -Orígenes del constitucionalismo americano and Nosotros, el Pueblo de los Estados Unidos- hinted of a possible interest by law students at the Universidad Carlos III de Madrid for an elective course on American constitutionalism. Thus, that was the reason behind El constitucionalismo americano, as a textbook for that course. Drafted around seven themes, they cover from the beginning of the seventeenth century and the fundamental laws that English settlers brought with them at their early landings on the American continent, to the constitutional Amendments and U.S. Supreme Court decisions of the second half of the twentieth century. Thus, the history of the United States has been divided into seven periods: the British colonial period; the American Revolution; the Federalist effort; the early Amendments and Supreme Court decisions; the Civil War and Reconstruction era; the Progressive era and the New Deal; and the Civil Rights period. For each period, some of the main relevant constitutional events get analyzed. Each theme includes a historical and legal presentation of the period, followed by the primary sources directly related to the events described. Assuming the targeted students may not be very familiar with the overall history of the United States, brief biographical notes are added for the most prominent personalities mentioned in the narrative. As a textbook, each theme includes a number of questions for the students to develop. (Incidentally, the course made it to OpenCourseWare, where its English version got a somewhat good response, receiving one of the organization's awards for 2013.). This work was part of the author's PhD effort. = Determinados aspectos de la sociedad norteamericana muestran tener una atracción especial para todo el mundo, al margen de creencias políticas y sociales. A menudo esas características tan familiares son las más frívolas del 'American way', mientras que rasgos más profundos e importantes de esa compleja nación parecen pasar desapercibidos más allá de sus fronteras, aunque su influencia sea manifiesta. La tecnología, negocios, comercio, cultura, etc., actuales están todos profundamente marcados por los 'ways' -maneras- de ese país. Sin duda alguna el sistema constitucional norteamericano es uno de esos 'rasgos ocultos' que, al margen de circunstancias locales y pequeños detalles, es omnipresente en lo que llamamos 'el mundo occidental'. Las respuestas a anteriores trabajos del autor -Orígenes del constitucionalismo americano and Nosotros, el Pueblo de los Estados Unidos-hicieron entrever un posible interés por parte de los estudiantes de Derecho de la Universidad Carlos III de Madrid hacia una asignatura optativa sobre el constitucionalismo norteamericano. De ahí surgió, como manual para ese curso, El constitucionalismo americano. Redactado en siete temas, cubre desde los inicios del siglo XVII y las normas fundamentales que los colonos ingleses llevaron a sus primeros asentamientos, hasta las Enmiendas y decisiones del Tribunal Supremo norteamericano sobre derechos civiles en la segunda mitad del siglo XX. De esta forma, la historia de los Estados Unidos se ha dividido en siete periodos: el periodo colonial británico, la revolución americana, el proceso federalista, las primeras Enmiendas y decisiones del Tribunal Supremo de los Estados Unidos, la guerra civil y la Reconstrucción, la era progresista y el New Deal, y el periodo de los derechos civiles. En cada periodo se estudian algunos de los eventos constitucionales más relevantes y de carácter universal. Cada tema incluye una presentación histórica y jurídica del periodo, seguida de las fuentes primarias relacionadas directamente con los eventos descritos. Suponiendo que los estudiantes a quienes va dirigido el manual podrían no estar muy familiarizados con la historia general de los Estados Unidos, se han añadido unas breves notas biográficas sobre los personajes mencionados en la narrativa. Al ser un manual de trabajo, se han incluido algunas cuestiones sobre los temas tratados para que los estudiantes pueden desarrollar los conocimientos aprendidos. (A título anecdótico, la versión on-line del manual en inglés recibió en 2013 uno de los premios de OpenCourseWare.) Este trabajo ha sido parte de los estudios doctorales del autor.